Combined dip/spin coating deposition of Ni/CeO2 and Ni/CeO2-Al2O3 onto 3D printed AlSi10Mg Periodic Open Cellular Structures (POCS) - Cristina Italiano; Gabriel Marino; Minju Thomas; Benjamin Hary; Steve Nardone; Simon Richard; Assia Saker; Damien Tasso; Nicolas Meynet; Pierre Olivier; Fausto Gallucci; Antonio Vita (Applied Surface Science Advances)
The effect of catalyst formulations and coating procedures on the deposition of thin active layers based on Ni/CeO2 and Ni/CeO2-Al2O3 onto AlSi10Mg Periodic Open Cellular Structures (POCS) with cylindrical shape (10 mm diameter and 15 mm length) was experimentally assessed in this work. An aqueous liquid medium based on water, glycerol, and polyvinyl alcohol was used for powder dispersion, while a combined dip- /spin- coating technique was chosen for washcoat deposition on metallic 3D printed structures characterized by Body-Centered Cubic (BCC) and Kelvin unit cells. The rheological behaviour of the prepared slurry was also studied. Multiple depositions with intermediate flash drying steps at 450 °C were carried out. Washcoat loads of about 15 % (0.1 g cm−3) were obtained. The used powders were characterized by BET, XRD and pycnometry, instead, the as built and activated supports were characterized by SEM/EDX and pycnometry. No pore clogging phenomena were observed and irrespective of the geometry used, the layers are deposited homogeneously. Adhesion of the deposited layers, evaluated by means of accelerated stress test in ultrasound bath, pointed out that the thermal/anodization pre-treatment of support as well as the use of Disperal P2® as primer, play a crucial role in achieving high mechanical stability associated with weight loss between 0.86 and 12.7wt %. Finally, preliminary catalytic activity tests were performed to evaluate the impact of POCS morphology on performance. The Kelvin structure exhibited superior efficiency in methane steam reforming (SR) at low temperatures, attributed to its optimized pore network and improved distribution of the active phase.